2016
DOI: 10.1016/j.cortex.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Two insular regions are differentially involved in behavioral variant FTD and nonfluent/agrammatic variant PPA

Abstract: The non-fluent/agrammatic variant of primary progressive aphasia (nfvPPA) and the behavioral variant frontotemporal dementia (bvFTD) are focal neurodegenerative disorders belonging to the FTD-spectrum clinical syndromes. NfvPPA is characterized by effortful speech and/or agrammatism and left frontal atrophy, while bvFTD is characterized by social-emotional dysfunction often accompanied by right-lateralized frontal damage. Despite their contrasting clinical presentations, both disorders show prominent left ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 61 publications
(65 reference statements)
8
42
0
Order By: Relevance
“…3D T1-weighted images with a magnetization-prepared rapid gradient echo sequence (MPRAGE) were obtained from patients and controls using either a 1.5 31 , 3 31 , or 4 Tesla 32 scanner.…”
Section: Methodsmentioning
confidence: 99%
“…3D T1-weighted images with a magnetization-prepared rapid gradient echo sequence (MPRAGE) were obtained from patients and controls using either a 1.5 31 , 3 31 , or 4 Tesla 32 scanner.…”
Section: Methodsmentioning
confidence: 99%
“…A flow diagram showing the identification and exclusion of studies is provided in Figure 1. Ultimately, a total of 37 studies were included in the meta-analysis, including 19 on bvFTD (one study included three bvFTD groups) (Rosen et al, 2002;Grossman et al, 2004;Boccardi et al, 2005;Kanda et al, 2008;Seeley et al, 2008;Ash et al, 2009;Kipps et al, 2009;Libon et al, 2009;Pardini et al, 2009;Hornberger et al, 2011;Farb et al, 2013;Massimo et al, 2013;Lagarde et al, 2015;Yokoyama et al, 2015;Dermody et al, 2016;Mandelli et al, 2016;Melloni et al, 2016;Buhour et al, 2017a;Bertoux et al, 2018) and 18 on ALS (Chang et al, 2005;Grosskreutz et al, 2006;Agosta et al, 2007;Mezzapesa et al, 2007;Thivard et al, 2007;Grossman et al, 2008;Cosottini et al, 2012;Tedeschi et al, 2012;Meoded et al, 2013;Cerami et al, 2014;Zhang et al, 2014;Devine et al, 2015;Raaphorst et al, 2015;Tavazzi et al, 2015;Zhu et al, 2015;Buhour et al, 2017b;Kim et al, 2017;Christidi et al, 2018…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…6,7 More recent studies showed alterations in functional connectivity with diffusion tensor imaging (DTI) and in brain activity with arterial spin labeling (ASL) or with BOLD imaging. [8][9][10][11] Changes in neuronal connectivity observed by DTI stresses the involvement of white matter structures. Mendes et al identified focal microhemorrhages in their cohort of FTD patients with unique focal prevalence for each sub-diagnosis.…”
Section: Introductionmentioning
confidence: 98%